Cytomegalovirus infection in hematologic malignancy settings other than the allogeneic transplant. Issue 2 (29th June 2017) - Marchesi, F.; Pimpinelli, F.; Ensoli, F.; Mengarelli, A.
Abstract: Cytomegalovirus (CMV) infection in clinical settings other than the allogeneic transplant represents a poorly explored issue. Thus, we performed a comprehensive review of the medical literature about CMV infection in patients undergoing autologous hematopoietic stem cell transplant and in other nontransplant‐related hematologic patients. In autologous hematopoietic stem cell transplant, a CMV reactivation is reported to occur in up to 41% of CMV seropositive patients, when a prospective monitoring of antigenemia and/or viremia by polymerase chain reaction was adopted. However, more contained frequencies, up to 12%, have been reported when the monitoring criteria were based on a clinically driven diagnostic strategy. The most relevant risk factors appear to be CD34 + selected autografts, total body irradiation, and prior treatment with Alemtuzumab, Fludarabine, or Bortezomib, respectively. Other possible risk factors (ie, prior treatment with Rituximab, T‐cell lymphomas, and pretransplant HBcIgG seropositivity) are still debated. In nontransplant settings, the data are very heterogeneous; thus, CMV infection incidence and risk factors are more difficult to establish. Overall, the rate of CMV infection/reactivation ranges between 2 and 67%. High‐dose steroids, advanced disease, poor performance status, and treatment with Alemtuzumab, Fludarabine, Bortezomib, and Rituximab appear as the most relevant, though putative, risk factors. Intravenous Ganciclovir represents the gold standard for first‐line treatment of CMV infection in these patients. Oral Valganciclovir and Foscarnet are other possible options. Extensive prophylaxis and preemptive therapy are not generally recommended, with the exception of high‐risk patients.